Dietary Echium Oil Increases Long-Chain n–3 PUFAs, Including Docosapentaenoic Acid, in Blood Fractions and Alters Biochemical Markers for Cardiovascular Disease Independently of Age, Sex, and Metabolic Syndrome. Issue 4 (19th February 2014) - Kuhnt, Katrin; Fuhrmann, Claudia; Köhler, Melanie; Kiehntopf, Michael; Jahreis, Gerhard
Abstract: Dietary supplementation with echium oil (EO) containing stearidonic acid (SDA) is a plant-based strategy to improve long-chain (LC) n–3 (ω-3) polyunsaturated fatty acid (PUFA) status in humans. We investigated the effect of EO on LC n–3 PUFA accumulation in blood and biochemical markers with respect to age, sex, and metabolic syndrome. This double-blind, parallel-arm, randomized controlled study started with a 2-wk run-in period, during which participants ( n = 80) were administered 17 g/d run-in oil. Normal-weight individuals from 2 age groups (20–35 and 49–69 y) were allotted to EO or fish oil (FO; control) groups. During the 8-wk intervention, participants were administered either 17 g/d EO (2 g SDA; n = 59) or FO [1.9 g eicosapentaenoic acid (EPA); n = 19]. Overweight individuals with metabolic syndrome ( n = 19) were recruited for EO treatment only. During the 10-wk study, the participants followed a dietary n–3 PUFA restriction, e.g., no fish. After the 8-wk EO treatment, increases in the LC n–3 metabolites EPA (168% and 79%) and docosapentaenoic acid [DPA (68% and 39%)] were observed, whereas docosahexaenoic acid (DHA) decreased (−5% and −23%) in plasma and peripheral blood mononuclear cells, respectively. Compared with FO, the efficacy of EO to increase EPA and DPA in blood was significantly lower (∼25% and ∼50%, respectively). A higher body mass index (BMI) was associated with lower relative and net increases in EPA and DPA. Compared with baseline, EO significantly reduced serum cholesterol, LDL cholesterol, oxidized LDL, and triglyceride (TG), but also HDL cholesterol, regardless of age and BMI. In the FO group, only TG decreased. Overall, daily intake of 15–20 g EO increased EPA and DPA in blood but had no influence on DHA. EO lowered cardiovascular risk markers, e.g., serum TG, which is particularly relevant for individuals with metabolic syndrome. Natural EO could be a noteworthy source of n–3 PUFA in human nutrition. This trial was registered at clinicaltrials.gov as NCT01856179.